Absence of Meckel Cave: A Rare Cause of Trigeminal Neuralgia - Jain, A.; Muneer, M.S.; Okromelidze, L.; McGeary, R.; Valluri, S.K.; Bhatt, A.A.; Gupta, V.; Grewal, S.S.; Cheshire, W.P.; Middlebrooks, E.H.; Sandhu, S.J.S. (American Journal of Neuroradiology, 2021)
SUMMARY: Trigeminal neuralgia is a debilitating condition with numerous etiologies. In this retrospective case series, we report a cohort of patients with a rarely described entity, absence of Meckel cave, and propose this as a rare cause of trigeminal neuralgia. A search of the electronic medical record was performed between 2000 and 2020 to identify MR imaging reports with terms including “Meckel’s cave” and “hypoplasia,” “atresia,” “collapse,” or “asymmetry.” Images were reviewed by 2 blinded, board-certified neuroradiologists. Seven cases of the absence of Meckel cave were identified. Seven patients (100%) had ipsilateral trigeminal neuralgia and ipsilateral trigeminal nerve atrophy, suggesting an association between absence of Meckel cave and trigeminal neuralgia. Absence of Meckel cave is a rare entity of unknown etiology, with few existing reports that suggest the possibility of an association with trigeminal neuralgia. Its recognition may have important implications in patient management. Future studies and longitudinal data are needed to assess treatment outcomes and added risks from surgical intervention in these patients.TNtrigeminal neuralgia